The Role of Madrasah Heads in Organizing the Improvement of Educational Services - Herman Herman (Seutia Hukamaa Cendekia, 2024)
In this era of globalization, the role of madrasah principals determines the quality of education services. This study aims to determine the role of madrasah principals in organizing to improve educational services. This research uses a qualitative approach with descriptive methods. Data collection techniques are done through observation, interviews, and document studies. At the same time, data processing techniques use Sugiyono's theory by reducing data (data reduction), presenting data (data display), and verifying data (concluding). The results showed that the role of the madrasah head in organizing towards improving educational services is to determine the work specialization or duties of teachers and employees, clarify the delegation of authority and responsibility of teachers and employees, and tighten control of the chain of command of the hierarchical structure or the position and function of teachers and employees in the madrasah. The results of this study can be recommended to the Head of the District/City Office of the Ministry of Religious Affairs to strengthen the organization and the leadership of madrasah principals to improve the quality of education services.